KETERAMPILAN SENI LUKIS TANGAN DENGAN HENNA MENUJU HENNA ARTIST - Sri Irtawidjajanti; Jenny Sista Siregar; Salsabila Salsabila Tri Ramadhan; Debyas Khalifah Sadellas; Fatimatuzahro; Anggie Kartika Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract 138 State Junior High School Jakarta have Open Junior High School program, because of the bad economic condition of the parents so that the big part of the graduates choose the work, make, a small business by the own skill. Only a little part who coninue their education to mote high level. Study Program of Cosmetology Education (S1) and (D3), in the 2021 academic year, the activities given to Community Service are